The Effect of Company Size, Systematic Risk and Independent Commissioners on Disclosure of Intellectual Capital - Petty Aprilia Sari; Imam Hidayat (EAJ (Economic and Accounting Journal), 2020)
The purpose this study is to determine the effect of company size, systematic risk and independent commissioners on intellectual capital disclosure in banking companies listed on the Indonesia Stock Exchange. The dependent variable is disclosure of intellectual capital, while the independent variable is company size, systematic risk and independent commissioners .This riset was conducted on banking companie listd on the Indonesia Stock Exchange (IDX) by accesing secondary data on annual reports for the 2015-2018 period. The results of the sample selection were 35 banking companies. The sample method used in this study is to use no-probability sample method with the sample technique chosen is purposive sample. The analysis used in this research is panel data regression analysis. The partial evaluation hypothesis testing results show that firm size and systematic risk have a significant positif effect on intellectual capital disclosure, while independent commissioners do not have a significant negatif effect on intellectual capital *disclosure